Effects of supplementing rumen-protected methionine and lysine on milk performance and oxidative status of dairy ewes - Mavrommatis, Alexandros; Mitsiopoulou, Christina; Christodoulou, Christos; Kariampa, Paraskevi; Simoni, Marica; Righi, Federico; Tsiplakou, Eleni (My University, 2021)
There is limited information on the impact of dietary supplementation with separate rumen-protected (RP) amino acids (AA), or with their combination, on ewes' oxidative status. Sixty ewes were divided into five groups; C: basal diet (control); M: basal diet + 6 g/ewe RP methionine; L: basal diet + 5 g/ewe RP lysine; LML: basal diet + 6 g methionine and 5 g lysine/ewe; and HML: basal diet + 12 g methionine + 5 g lysine/ewe. Milk's fat content increased in RP-AA fed ewes, while that of protein in M and L only. In blood plasma, the malondialdehyde (MDA) content was reduced in the M, LML, and HML compared to C-fed ewes. An increase in glutathione transferase activity in the blood plasma of the M and LML compared to the C and HML-fed ewes were found. In milk, lower values of the ferric reducing ability of plasma (FRAP) in the LML and HML-fed ewes and of 2,2'-Azino-bis 3-ethylbenzthiazoline-6-sulfonic acid (ABTS) in LML only, were found. Lysine increased milk's FRAP values and MDA content. Both L and HML diets increased milk's protein carbonyls content. Methionine improves the organism's oxidative status, without adversely affecting milk's oxidative stability. Lysine dietary inclusion affects negatively the oxidative stability of milk.
Keywords: Amino acids; Antioxidants; Blood; Enzymes; Ewes; Malondialdehyde; Milk; Oxidative stress indicators